Building Intercultural Understandings Through Global Literature. (2nd April 2015) - Martens, Prisca; Martens, Ray; Doyle, Michelle Hassay; Loomis, Jenna; Fuhrman, Laura; Furnari, Christie; Soper, Elizabeth; Stout, Robbie
Abstract In this article the authors share how they use global literature picturebooks with pre‐kindergarten, kindergarten, and first grade children in the context of A Curriculum That is International to develop the children's intercultural understandings. The picturebooks, shared through read alouds, individual and partner reading, and browsing, is focused particularly on children's personal identities as cultural beings and their identifying issues for which they take action to make the world a better place. In addition, the illustrations are discussed to develop the children's understandings of creating meaning through art. The authors argue that by through experiences with global literature children develop richer understandings of themselves as complex cultural beings and a perception of themselves as capable problem‐solvers who identify issues and take action to solve them.